Exploring the factors underlying successful publication following participation in an Author Assist service - Banner, Megan (Division of Emergency Medicine, 2017)
Author Assist is an initiative of the African Journal of Emergency Medicine (AfJEM) that pairs an experienced researcher with an author recently rejected for publication to assist with revision of the rejected article. This study explores the factors of the assistance process within partnerships that have achieved successful publication after resubmission and blind peer-review. It aims to improve Author Assist's ability to facilitate successful publication by identifying potential areas of focus that impact individual researcher development. A grounded theory, qualitative approach first looks at the assistance process for seven individuals via semi-structured interview. Structured surveys with a wider sample size of authors then provide feedback on specific components of the process and inform recommendations for improvements to the programme. Interviews are analysed by deductive placement of themes into inductively-developed categories. Participant stories within the African acute care context tend to be consistent with available literature describing current global challenges in overcoming barriers to scientific research and publication. Recounts of the Author Assist process are overwhelmingly positive, and frame the programme as a worthwhile, albeit time consuming, initiative that makes a substantial difference in the professional development of individuals, their ability to take on mentorship roles themselves, and their future success in scientific publication. Inductive build-up from interviews of effective components of the process, and suggestions for progression of the programme are confirmed by responses from other past participants. Common themes arising from author feedback include perceived pressure by assistants to complete work on time amidst other career demands; the effectiveness of the partnerships in addressing issues of language, structure, and submission requirements; and the desire for the programme to encompass the full research process. Assistant themes tend to mirror those of the authors. In addition, assistants suggest a more involved manuscript assessment by the journal, prior to commissioning a partnership. Also suggested is a redesign of the assistant database to categorise by type of assistance offered, rather than by topic expertise. The findings from this study confirm Author Assist's unique niche within emergency care development, and its effectiveness in supporting individual research careers. A number of reasonable and low cost improvements to the programme have been put forward for AfJEM to improve ability to facilitate successful publication.